Analysis on Relational-Understanding in Solving Problem for Field Independent Students - Yazidah, Nok Izatul; Argarini, Dian Fitri; Sulistyorini, Yunis (AT-TA'LIM, 2018)
The purpose of this study is to describe students’ relational understanding in solving problems for FI students. The subjects of this research are Senior High School students having field independent cognitive style in Malang and chosen randomly. The subjects consist of two students. Sheet of GEFT test, sheet of Combinatorial questions, and interview sheet were used in this study. The finding of the study showed that medium-academic achievement student had an ability on relational understanding as the same as the high-academic achievement student. Meanwhile, the process in solving problem made by the high-academic achievement student was likely similar to the accurate process in solving problems.